KONTRIBUSI ETOS KERJA DAN PELAKSANAAN SUPERVISI TERHADAP KINERJA GURU PADA SEKOLAH MENENGAH KEJURUAN (SMK) NEGERI 1 SUMATERA BARAT - Ilmiyati Rahmy Jasril (Universitas Negeri Padang, 2016)
This study aims to reveal contribution of work ethic and implementation of supervision toward the teacher’s performance both partially and simultaneously. This was a correlational study. The population and sample of this study was teachers of vocational high school (SMK) Negeri 1 West Sumatera. The sample was selected by using stratified proportional random sampling techniques. The data were collected by using questionnaire with Likert-scale model. The data were analysed using correlation and multiple regression techniques with stepwise method. The results of this study indicate that there was a significant contribution work ethic and implementation of supervision toward the teacher’s performance of vocational high school (SMK) Negeri 1 West Sumatera both partially and simultaneously.The findings and recommendations of the study are useful to improvement of teachers’ performance